Globalization and labour in the twenty-first century - Burgmann, Verity (2016)
Globalisation has adversely affected working-class organisation and mobilisation; but international labour movement demobilisation is not necessarily an irreversible trend. Globalisation has prompted workers and their organisations to find new ways to mobilise. This book examines international labour movement opposition to globalisation. It chronicles and critically scrutinizes the emergence of distinctively new forms of labour movement organisation and mobilisation that constitute creative initiatives on the part of labour, which present capitalism with fresh challenges. The author identifies eight characteristics of globalisation that have proven problematic to workers and their organisations and describes and analyses how they have responded to these challenges since 1990 and especially in the past decade. In particular, it focuses attention on new types of labour movement organisation and mobilisation that are not simply defensive reactions but are offensive and innovative responses that compel corporations to behave more responsively and responsibly towards employees and society at large. This book will be of interest to students and scholars of globalisation, political economy, labour politics, economics, Marxism and sociology of work.